The perils of aiming too high: discrepancy between goals and performance in individuals with depressive symptoms - Arens, Elisabeth A.; Schwieren, Christiane; Barnow, Sven (Journal of behavior therapy and experimental psychiatry, 2018)
BACKGROUND AND OBJECTIVES: Negative evaluation processes play a pivotal role in the development and maintenance of depressive symptoms. However, it remains to be understood, whether evaluation processes in depression are impaired by maladaptive goal setting. METHOD: In a non-clinical sample (N = 50) of individuals with high (BDI-II-Score: 13-29) and low (BDI-II-Score: 0-3) levels of depressive symptoms goal setting prior to working on a cognitive task was measured. Goal feasibility was experimentally manipulated using an easy and a difficult version of the task. RESULTS: When goal feasibility was low, a high level of depressive symptoms was associated with setting unattainable goals. Whereas individuals with low level of depressive symptoms adjusted their goals to a lower (more realistic) level when task difficulty increased, individuals with high level of depressive symptoms initially adhered to significantly higher goals, so that their performance failed to meet their self-set standards. After depressed individual revised their goals downwards, their subsequent performance on the task also worsened. LIMITATIONS: The use of a non-clinical sample with self-reported depressive symptoms limits the generalizability of our findings to a clinical population. Future research would benefit from the use of a larger sample with patients suffering from clinical depression. CONCLUSIONS: The findings support the notion that negative evaluation processes in depressed individuals might be linked with their tendency to generate intractable conflicts between self-set inappropriate high goals and their own capacities to perform. However, the findings need to be confirmed in clinical samples to draw conclusions about the role of goal setting in negative evaluation processes in depression.